Nanny Ogg's cookbook : including recipes, items of antiquarian lore, improving observations of life, good advice for young people on the threshold of the adventure that is marriage, notes on etiquette & many other helpful observations that will not offend the most delicate sensibilities /: including recipes, items of antiquarian lore, improving observations of life, good advice for young people on the threshold of the adventure that is marriage, notes on etiquette & many other helpful observations that will not offend the most delicate sensibilities. (2001) - Unknown
No abstract available